The effect of organic matter on soil organic carbon and water spinach grown in gold mine tailings - Aprila, Zahra Ardelia; Hindersah, Reginawanti; Sofyan, Emma Trinurani (Current Research in Agricultural Sciences, 2023)
The disposal of tailings generated from mining activities poses environmental challenges due to their low fertility and limited suitability for plant growth. This study aimed to investigate the potential of cow manure application in improving the organic-C content of tailings and enhancing the growth of water spinach (Ipomoea reptans). This experiment was laid out in a randomized block design with five treatments and five replications. The treatments involved the application of cow manure at different doses and control, which consisted of; (A) Control, (B) 150 g, (C) 300 g, (D) 450 g, (E) 600 g. The results revealed a significant increase in the organic-C content of tailings following the application of cow manure. The highest organic-C content of 7.47% was achieved with the application of 600 g of cow manure. The application of 150 g of cow manure resulted in the tallest plants with higher fresh and dry weights. The findings from this study underscore the importance of organic amendments in enhancing the organic-C content and promoting plant growth in low fertility growth medium. Further research on the long-term effects and optimization of cow manure application in tailing-based growth substrates is recommended to enhance soil fertility and maximize plant productivity.